Hidden hunger in Europe: a review on determinants, fragmented policy responses, and implementation barriers - Gallina, Alessandro L.; Otay, Suzan; de Frutos-Lucas, Jaisalmer; Buso, Marion; Moral Martinez, Paula; Cashman, Kevin D.; Kiely, Mairead E.; Astley, Siân (Frontiers in Nutrition, 2025)
Despite significant improvements in food security and healthcare, micronutrient deficiencies – or “hidden hunger” – remain a widespread and under-recognized public health issue across Europe. These deficiencies impair metabolic, cognitive, and immune functions, and are linked to non-communicable diseases and increased morbidity in an aging European population. This policy review, undertaken within the European Union (EU)-funded Zero Hidden Hunger EU project, examines the demographic, socioeconomic, and geographical drivers of micronutrient deficiencies in Europe and evaluates existing national and EU-level policy responses. Vulnerable populations, including children, women of reproductive age, older adults, low-income households, and those living in low-UV regions, face disproportionately high risks due to intersecting biological, environmental, and social factors. The review also identifies substantial variation in national fortification strategies, revealing fragmented regulatory frameworks and inconsistent implementation. While EU legislation offers a harmonized structure for voluntary fortification, its flexibility has enabled broad national divergence, limiting the coherence and impact of public health efforts. Evidence from national policies illustrates both the potential and the shortcomings of current approaches. This review calls for more equity-oriented, mandatory, and evidence-based public health strategies, to address micronutrient malnutrition, including fortification, supported by comprehensive nutrition education and social protection measures. Initiatives such as the Zero Hidden Hunger EU project represent a critical opportunity for participatory policy co-creation, aiming to close data gaps and advance more inclusive and sustainable nutrition policies across Europe.